Joint hypermobility as a functional connective tissue disorder: clinical implications and the need for standardization of support protocols - Wawrzynów, Marta (Запоріжжя: ТДАТУ, 2026)
Joint hypermobility is most defined as an increased range of motion within the joints; however, this definition fails to capture its complexity. It is currently understood as a multidimensional condition resulting from the interaction among connective tissue properties, neuromuscular control, and biochemical processes that influence the function of the musculoskeletal system. Despite increasing clinical awareness, hypermobility remains underrecognized, particularly in cases lacking a formal diagnosis (hEDS, HSD; Castori et al., 2017; Malfait et al., 2017).
Keywords: Joint hypermobility; musculoskeletal system